A survey of the density, distribution and Schistosoma japonicum infection of Oncomelania quadrasi collected from selected barangays in Tacloban City - Limpiado, Charity Joy E. (2016)
Oncomelania quadrasi carries and transmits the infectious parasite, Schistosoma japonicum, which up to the present continues to infect about a million people in the Philippines making Schistosomiasis a remaining public health threat in the country. Whereas the administration of the drug praziquantel is effective in controlling the morbidity of schistosomiasis, snail control by targeting snail habitats is still one of the best ways for preventing the parasite's transmission. Tacloban city is located in the province of Leyte, one of the 24 provinces identified to be endemic of the disease. This study identified 3 barangays, strategically located in the city, that harbor O. quadrasi. Through snail intensive search and ring sampling technique, Barangay Sta. Elena was found to have the highest snail density and distribution, while Brgy. 82 Marasbaras had the least. Analysis on the microscope examination results showed that S. japonicum infection rate in collected snails was highest in Brgy. Sta. Elena, followed by Brgy.82 Marasbaras and then the least infected was Brgy. Paglaum.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Schistosoma japonicum infection; Science and technology